Use of genetic markers to identify the illegal trade of billfish in the second largest fishing warehouse of Latin America - Rodrigues Júnior, Carlos Egberto [UNESP]; Daniel, Sandro Natal [UNESP]; Martins, Diego Galetti [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fabio [UNESP] (Wiley, 2020)
Billfish are oceanic pelagic species that are often caught by tuna fleets and are of great interest for sport fishing. Two species of billfish have specific legislation prohibiting their marketing and export in Brazil. DNA barcoding is a universal system of molecular identification based on a sequence of mitochondrial DNA cytochrome oxidase subunit I (COI), which serves as a diagnostic genomic marker in each species. The barcode DNA technique was used to identify billfish marketed in the second largest fishing warehouse in Latin America, the CEAGESP (Companhia de Entrepostos e Armazéns Gerais de São Paulo), located in São Paulo, Brazil. Seventy-nine samples of billfish were collected during three inspection visits carried out by Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis. After DNA sequencing, 70 samples (88.60%) were identified to the species level; 21 (30.00%) were identified as Xiphias gladius, 43 (61.42%) as Istiophorus platypterus and six (8.57%) as Kajikia albida. The sale of this latter species is prohibited in Brazil and it is considered Vulnerable on the list of endangered species of the IUCN and in the official list of species of endangered Fauna – Fish and Aquatic Invertebrates. Molecular analyses proved to be very efficient at uncovering irregularities in the identification of the white marlin (K. albida), which was traded illegally in CEAGESP, demonstrating the ineffectiveness of the current monitoring techniques used and emphasizing the need for the adoption of better public policies for the conservation of the species.
Keywords: billfish; DNA barcoding; Istiophoridae; sailfish; swordfish; white marlin; Xiphiidae